Partisipasi Masyarakat Dalam Kegiatan Musyawarah Perencanaan Pembangunan Desa (Musrenbangdes) Di Desa Sumberejo Kabupaten Madiun - Lukman Arif; Garneza Merlyana Alfianti; Ananda Eka Putri Trisnawati; Azzahrah Putri Arindi; Kumala Abhitah Syahsubagyo (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Communities must have active participation in development. Because the community is no longer the object of development but the subject of development. In 2023, Madiun Regency won an award in the 2024 RKP National Musrenbang with a special category of Alternative KPBU Financing Innovation for Infrastructure Provision. This is of course also supported by the quality of Musrenbang activities at the District and Village levels. Because, Development Planning must start from the bottom, namely at the village level. The Village Musrenbang is one of the forums for the community to participate in development plans at the village level. Sumberejo Village is one of the villages in Madiun Regency that has a high level of community attendance in the Village Musrenbang. The purpose of this research is to describe the participation of the community of Sumberejo Village and to describe the high level of community participation. This research uses descriptive qualitative methods with data from interviews, observations, and documentation as primary data, as well as secondary data in the form of literature that has relevance to this research. The results of this study based on Dwiningrum's form of community participation, namely attendance at meetings, discussions, contribution of ideas, and response or rejection of the program offered, show that the participation of the community of Sumberejo village, Madiun district, in the Village Musrenbang activities is good.